Students’ Perception on Online Learning during the Covid-19 Pandemic - Heni Novita Sari; Putri Nurmaulida (Universitas Pahlawan Tuanku Tambusai, 2023)
The pandemic of COVID-19 has forced the Indonesian government through its Ministry of Education and Culture to implement policies moving face-to-face classroom to online learning. The aim of this research is to knowing the students’ perception on online learning during the covid-19 pandemic at SMKS IPTEK sanggabuana. This research used a descriptive-qualitative method. in collecting the data, the researcher used questionnaire, there were 30 students from OTKP (Otomatisasi dan Tata Kelola Perkantoran/Automation and Office Governance) class of SMKS IPTEK Sanggabuana participated in this research. Based on the analysis the data, the researcher found conclusion of students’ perception toward online learning during the covid-19 pandemic gets positive perception because it is flexible and effective. This can be seen from percentage of the data, 56% students answered agree for interctivity, 58% agree in independence, 38% agree in accessibility, and 56% students answered agree in enrichment. It means students can adapt the online learning system to temporarily replacing conventional learning during Covid-19 pandemic. Even though the students found the difficulties to understand the material in online learning. Keywords: Students’ Perception, Online Learning, Covid-19 Pandemic